Synthesis, mechanistic and biological evalution of novel bis-sydnone styrylketone as antiproliferative and antioxidant agents - Nik Yusoff, Nik Mohd. Idris; Ridzwan, Irna Elina; Bakhtiar, Muhammad Taher; Abdualkader, Abdualrahman Mohammed (2018)
Various literature sources have documented that sydnones are important bioactive molecules with a wide spectrum of activities involving the anti-proliferative and anti-inflammatory actions. Phenyl styrylketones and their derivatives as members of the chalcone family have also been reported as significant biological agents. The current study was initiated to evaluate in vitro cytotoxic and anti-inflammatory activity of sydnone-based compounds including some novel sydnone-styrylketone hybrids. The classical cyclodehydration of N-nitroso amino acids was applied in the preparation of the sydnone ring. Aldol condensation was utilized to join two sydnone rings by a styrylketone linker. Compounds identity was confirmed using FTIR, NMR and MS spectroscopy. MTT assay was used to evaluate the cytotoxicity of the synthesized compound. ELISA test was performed to investigate the COX-1/COX-2 inhibitory activity. The binding of sydnones with COX enzymes was examined by Glide docking and the Molecular Mechanics-Generalized Born Surface Area (MM-GBSA). The drug-likeness scores and membrane permeability of the compounds were also in silico predicted. Twenty-five sydnone-containing compounds were synthesized. Compounds 46-48 and 56-58 were reported as new sydnone derivatives. Compounds 61-63 were synthesized as novel structures containing two sydnone rings linked via α,β-unsaturated ketone. The structure of the synthesized compounds was confirmed by FTIR, 1H NMR, 13C NMR and ToF-MS analyses. All compounds exhibited low cytotoxicity especially against normal cell lines (IC50 in the range of mM). Only compound 45 had a significant antiproliferative activity against prostate (IC50 = 42 μM) and breast (IC50 = 63 μM) cancer cell lines. The in vitro COX inhibition assay showed varied activity. Compounds 47, 51, 58 and 63 showed the most potent COX inhibitory effect at a concentration of 200 μM. Selectivity index showed that only compound 63 was a selective COX-2 inhibitor. Acetylation of the sydnone ring at C4 was detrimental to the cytotoxic activity while prolific for the anti-inflammatory effects (COX inhibition). Docking analysis showed that COX-2 selectivity was due to a favorable positive charged interaction between the sydnone ring of 63 and Arg513 in the catalytic region of COX-2. Compound 51 was hydrogen bonded to the guanidinium group of Arg513. The low inhibitory effect of 63 against COX-1 was due to an unfavorable polar interaction with His513 in the binding pocket of COX-1. Drug-likeness prediction disclosed that the compounds comply with Lipinski’s rule and CMC-like rule. Similarity search delineated that sydnone-styrylketone hybrids had common structural features with known anti-inflammatory agents. Prediction of permeability through the physiological membrane revealed a good pharmacokinetic profile with intestinal absorption more than 80% and a potential BBB penetration. In conclusion, the compounds were successfully synthesized and characterized. However, only two compounds 59 and 60 were not successfully prepared. The structure of 3-(4-chloro-3-nitrophenyl)sydnone 45 could be a lead molecule in designing potent chemotherapeutic agents. Compound 63 shared architecture and pharmacophoric characters with known selective COX-2 inhibitors (coxib family) making it a good candidate for designing selective and safe NSAID.